Old Order, New Order, NU Order (Existence of NU Today) - Afidatul Asmar (Journal of Nahdlatul Ulama Studies, 2020)
This paper attempts to explain the role and strategy of the Nahdlatul Ulama (NU) today, by making a comparison of the existence of the NU from the Old Order (ORLA), then in the New Order (ORBA) which finally according to the author produced the NU Order (ORNU). This research uses the library research method to answer the various ups and downs that lead to the design of the paradigm, methodology, and foundation of NU today. The results showed that the NU experienced ups and downs, becoming the largest Islamic organization during the Old Order. Then it became a political party during the New Order era. Then the final result explained that ORNU which was intended at this time was NU returned to their first goal of forming an NU organization to preach in the social and educational fields, not to engage in practical politics.